Value of cytology for detecting endometrial abnormalities in climacteric women receiving hormone replacement therapy. Issue 6167 (31st March 1979) - Studd, J W; Thom, M; Dische, F; Driver, M; Evans, T W; Williams, D
Abstract : Over six months 113 endometrial specimens from 110 menopausal women receiving hormone replacement therapy were examined by two cytologists and two histopathologists. Specimens were obtained by aspiration with the Isaacs cell sampler immediately before Vabra suction curettage, both procedures being performed in the outpatient department without anaesthetic. The histologists agreed with each other on the classification of 85 specimens (75.2%) and the cytologists agreed on the classification of 44 (38.9%). In only 15 cases (13.3%) did all four observers agree. Of the three cases of cystic or adenomatous hyperplasia detected histologically, only one was diagnosed by cytology. Furthermore, both cases of adenocarcinoma escaped detection by cytology, though a third case–later confirmed-"was suspected by one cytologist alone. Use of the Isaacs endometrial cell sampler cannot be advocated for routine screening of women with climacteric symptoms receiving hormone replacement therapy. Efforts should be made to establish the correct dose and duration of treatment with an oestrogen-progestogen preparation in order to avoid over-stimulating the endometrium and the need for regular screening for endometrial abnormalities.